Corrigendum to "2-Aminobenzene-1, 3-dicarbonitriles as green corrosion inhibitor for mild steel in 1 M HCl: Electrochemical, thermodynamic, surface and quantum chemical investigation" [Journal of the Taiwan Institute of Chemical Engineers 49 (2015) 229-239] - Verma C.; Quraishi M.A.; Singh A. (My University, 2025)
[No abstract available]